Peran Customer Value dalam Memediasi Green Marketing terhadap Keputusan Pembelian Mobil Low Cost Green Car (LCGC) di Kota Jambi - Anaseputri Jamira; Andri Yandi (J-MAS (Jurnal Manajemen dan Sains), 2019)
The purpose of this study is to examine the relationship between green marketing, customer value, and purchasing decision of Low Cost Green Car (LCGC) in Jambi City. To analyze customer value as mediating or intervening variable, Path Analysis with SPSS for Windows 21.0. software is used to confirm the relationship between variables. There are 120 respondents who are as Low Cost Green Car (LCGC) consumer and decision maker of buying it in Jambi City, that participated in this research by fulfill questionnaires. The results show that green marketing and customer value are important variables which each variable has influence on purchasing decision, and customer value acts as a mediating variable of green marketing to purchasing decision. This study needs to be followed up again to see what factors are can influence the decision to purchase a Low Cost Green Car (LCGC) in Jambi City.